Sustainable territories: legitimizing conservation in biosphere reserves - Zalles, Jorje I. (2022)
Biosphere reserves constitute a management proposal that aims to reconcile multiple types of land use on a surface area that is representative of the planet´s ecological and cultural diversity. Among their objectives are safeguarding the ecological integrity of core areas dedicated to conservation, which ultimately means taking into account the needs of those human populations inhabiting the reserve. This essay postulates that in order to legitimize conservation efforts within biosphere reserves it is necessary to activate two distinct processes: sustainability and territorialization. In other words, biosphere reserves need to be considered as sustainable territories if they are to achieve their conservation goals. In this case, environmental sustainability is accomplished through the provision of ecosystem services by means of establishing multifunctional landscapes, whereas social sustainability implies the institutionalization of social processes. Territorial appropriation of the reserve on the part of its inhabitants should furthermore be sought. Brought about jointly, environmental sustainability, social sustainability, and territorialization would enable biosphere reserves to become sustainable territories, thus underpinning their conservation potential.